Um produto viável mínimo para gestão ambiental: um action research - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Environmental consulting firms deal with a variety of clients across multiple projects. In this context, the large amount of information to be managed by professionals in the fi- eld makes the use of management tools not only useful, but essential. This study aims to describe an action research, conducted in collaboration with the project sponsor, for the development of an environmental management tool. The action research involved several iterations of design and testing, evaluating the efficiency and effectiveness of the product and allowing the development team to refine the tool and achieve a sta- ble version of a Minimum Viable Product. The results of these tests provided a robust justification for the implementation of the system in a production environment. KEYWORDS: Web system; ESG; Environmental management; MVP.
Keywords: Engenharia de software; Sistema web; Gestão ambiental; Software engineering; Environmental management; Web system; CNPQ::CIENCIAS EXATAS E DA TERRA